2022
DOI: 10.3390/su141912396
|View full text |Cite
|
Sign up to set email alerts
|

Online Flipped and Gamification Classroom: Risks and Opportunities for the Academic Achievement of Adult Sustainable Learning during COVID-19 Pandemic

Abstract: The online traditional and the online flipped classroom approaches have been adopted worldwide in higher education during the prolonged city lockdowns. Research has suggested that gamification is a technopedagogy which can be integrated into these approaches to promote learning outcomes. Hence, this study aims to uncover various risks and opportunities involved in adopting the online flipped and gamified classroom approaches, especially in terms of their impact on academic achievement, for ensuring sustainable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…These may not necessarily favor self-efficacy, but guide one on the path towards it [63]. Despite these potential benefits, the study by Ng and Lo [64] warns that gamification can negatively affect student motivation, and interrupt their participation in learning activities when training has not been safeguarded. Technological and technical aspects are relevant to its effective implementation.…”
Section: Teaching Strategiesmentioning
confidence: 99%
“…These may not necessarily favor self-efficacy, but guide one on the path towards it [63]. Despite these potential benefits, the study by Ng and Lo [64] warns that gamification can negatively affect student motivation, and interrupt their participation in learning activities when training has not been safeguarded. Technological and technical aspects are relevant to its effective implementation.…”
Section: Teaching Strategiesmentioning
confidence: 99%
“…This is consistent with the study performed by Meccawy et al [93], in which they found the same positive appreciation of students towards immediate response systems. This strategy can be used for various purposes, namely, with a social-academic purpose, to activate previous knowledge, for assessment, and others [46,94,95]. Furthermore, immediate response system software is an easy-to-use tool that is available for free or at a very low cost.…”
Section: -2-2-pedagogical Practices That Promotes Participation Durin...mentioning
confidence: 99%
“…Students also mentioned that strategies based on gamification motivate them to participate more during synchronous sessions. It has already been shown that gamification promotes motivation since it emulates video gaming and keeps the attention of students while also generating a fun environment for learning [46,47].…”
Section: -2-2-pedagogical Practices That Promotes Participation Durin...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context generated by COVID-19, teachers had to change their usual teaching methodologies (Salvador-García, 2021;Ng & Lo, 2022); that is, going from a traditional teaching model to virtual teaching where their adaptation to change unlocked their insecurities and inexperience to use digital tools (Villarroel et al, 2021). The use of these tools during the pandemic required teachers to change their educational practices and teaching models (Marisa et al, 2020;Rincon-Flores & Santos-Guevara, 2021;Nair, 2022), forsaking their role as an information provider, to become a counselor or guide, since the knowledge is online and no longer needs someone to provide it (Páez-Quinde et al, 2022).…”
Section: Introductionmentioning
confidence: 99%